Climate Change and the Niger Delta Region - Adewumi, A. A.; Agunbiade, O. R.; Longe, O. O.; Fadiya, O. O.; Adewumi, I. K. (Advances in Social Sciences Research Journal, 2018)
The Niger Delta is located in the Atlantic coast of southern Nigeria where River Niger divides into numerous tributaries. It is the second largest delta in the world with a coastline spanning about 450 kilometres. It is the richest wetland in the world, highly diverse and supportive of numerous species of terrestrial and aquatic flora and fauna and human life. The Niger Delta is faced with myriads of environmental problems caused by climate change and the activities of multinational oil companies operating in the region. The occurrence of coastal erosion, rise in sea level, renewable resource degradation had been reported. Climate change has affected rainfall pattern with the consequent effect on vegetation and thus agriculture. Sea-level rise and repeated ocean surges will not only worsen the problems of coastal erosion that are already a menace in the Niger Delta, the associated inundation is increasing problems of floods, intrusion of sea-water into fresh water sources and ecosystems destruction thus destabilizing the mangrove, and affecting agriculture, fisheries and general livelihoods. Coastal erosion is the most important impact of sea level rise in the region and should be given high priority attention. With the distruption/destruction of the coastal ecosystem, loss of habitat and the climate getting warmer, the fish population is affected. Coastal erosion and flooding moulder the fertilizing eggs and fry of fishes thus affecting recruitment into the population. Several roads have been made impassable. Settlements in the coastal region, especially in Forcados, with some oil wells, have been uprooted by coastal erosion. It is predicted that Nigeria will lose about 9 billion as a result of the sea level rise while at least 80% of the people of the Niger Delta will be displaced due to the low level of the region. A participatory, integrated approach to development is the solution. Government-private-sector partnership as well as partnership with other actors should be an integral part of the integrated approach.